Charaterization of Candida species isolated from pregnant women with vaginal discharge attending anternatal clinic in parts of Edo State, Nigeria - Okodua, Marcellinus; Aderibigbe, Dorcas; Oni, Daniel Oyewole; Oni, Valentine Imade; Unuabonah, Faith; Iserhienrhien, Osamuyimen; Eyaufe, Aidevbo Otuyoma (Intelektual Pustaka Media Utama, 2025)
During pregnancy, women are more prone to vaginal infections due to immunological changes. These infections are mainly caused by different species of Candida, a reality that makes distinguishing Candida species vital since non-albicans strains often resist common antifungals, making accurate diagnosis key to better maternal outcomes. Therefore, this study aimed at isolating and characterizing Candida species from pregnant women with vaginal discharge. The sample size consisted of 220 subjects (151 pregnant and 69 non-pregnant women). Samples were collected following standards guidelines and analyzed for Candida by culturing on Sabouraud dextrose agar (SDA) and CHROMagerTM Candida (CAC). The overall prevalence of vulvovaginal candidiasis (VVC) was 34.55%, and VVC infection was more common among women >30 years. VVC infection was more common in women in their second trimester (48.05%). There was a significant difference with gestational age (p≤0.05). Candida albicans was the most common cause of VVC in both pregnant (75.86%) and non-pregnant (77.78%) subjects. There was no significant variation (p>0.05) in the species of Candida isolated from pregnant and non-pregnant women. Overall, C. albicans was the most common species isolated from pregnant women. This was followed by Candida krusei (10.34%), Candida dublinensis, Candida. glabrata (5.17% each) and Candida parapsilosis (1.72%); while mixed infection, both C. dublinensis and C. parapsilosis were found in 1.72%. Among the non-pregnant women, C. albicans was the most common species isolated, followed by C. dublinensis and C. glabrata (11.11% each). C. krusei and C. parapsilosis were not isolated from non-pregnant women. Routine screening of vulvovaginal candidiasis and other vaginal infections should be conducted during antenatal visits to enable early detection and treatment.